2011
DOI: 10.1111/j.1559-1816.2011.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Exchange at Work and Emotional Exhaustion: The Role of Personality1

Abstract: Unbalanced social exchange processes at work have been linked to emotional exhaustion. In addition to organizational factors, individual differences are important determinants of reciprocity perceptions. This study explored whether broad and narrow personality traits were associated with perceived lack of reciprocity (organizational and interpersonal level), and whether personality moderated the relationship between reciprocity and emotional exhaustion, in a sample of 322 civil servants. Extraversion, agreeabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 106 publications
(151 reference statements)
0
14
0
Order By: Relevance
“…Interestingly, Dagher et al (2015) also found that self-efficacy has a significant positive influence on the three dimensions of employee engagement (vigor, dedication, and absorption) using a sample of employees in the service industry from Lebanon. On the other hand, some scholars argued that personality traits have a moderating effect on the relationship between Perceived Supervisor Support (PSS) and frontlines' service performance and that the Social Exchange Theory (SET) is the best context to explain it, since employees with different personality traits, though working under the same organizational practices, will form different perceptions (Petrou et al, 2011;Ruppel et al, 2013;Fullarton et al, 2014;He et al, 2015) and therefore develop different levels of obligation to return the organization's favors (Oentoro et al, 2016).…”
Section: The Impact Of Individual Characteristics and Personal Resourcesmentioning
confidence: 99%
“…Interestingly, Dagher et al (2015) also found that self-efficacy has a significant positive influence on the three dimensions of employee engagement (vigor, dedication, and absorption) using a sample of employees in the service industry from Lebanon. On the other hand, some scholars argued that personality traits have a moderating effect on the relationship between Perceived Supervisor Support (PSS) and frontlines' service performance and that the Social Exchange Theory (SET) is the best context to explain it, since employees with different personality traits, though working under the same organizational practices, will form different perceptions (Petrou et al, 2011;Ruppel et al, 2013;Fullarton et al, 2014;He et al, 2015) and therefore develop different levels of obligation to return the organization's favors (Oentoro et al, 2016).…”
Section: The Impact Of Individual Characteristics and Personal Resourcesmentioning
confidence: 99%
“…Conscientious people are described as punctual, well organized (Petrou, Kouvonen & Maria, 2011), methodological, dependable and risk-averse (Goldberg, 1990). Conscientiousness is positively correlated with performance and job satisfaction (Barrick & Mount, 1991; Judge, Heller & Mount, 2002; Judge, Higgins, Thoresen & Barrick, 1999), achievement motivation and task accomplishment rather than with economic rewards (Stewart, 1996).…”
Section: Proposed Modelmentioning
confidence: 99%
“…The support from their supervisors, such as providing resources and information to facilitate their job, could make it easy for extroverts to perform better in service recovery. Moreover, Petrou et al (2011) found that 302 APJBA 8,3 extroverts are willing to perform better when they perceived an equality exchange relationship between them and the employer are existed in the workplace. Hence, it is expected that employees who are high in extraversion are likely to perform better in terms of service recovery after they have received support from their immediate supervisors.…”
Section: Extraversionmentioning
confidence: 99%
“…supervisors and management, it should induce in them the desire to support the organization (Blau, 1964;Eisenberger et al, 1986). Petrou et al (2011) argued that despite these findings, personality traits could lead to unexpected and adverse outcomes. Consistently, research by Ashill et al (2009) on service behaviors showed that personality traits can influence employees' performance in dealing with service failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation